Examination of Influencing Factors of Postgraduate Students’ E-learning Satisfaction, and Continuance Intention in Chengdu, China - Yang, Long (Scholar: Human Sciences, 2024)
Purpose: This study aims to investigate the factors that influence e-learning satisfaction, and continuance intention among postgraduate students in Chengdu, China. The key variables are system quality, information quality, confirmation, service quality, perceived usefulness, students’ satisfaction and continuance intention Research Design, Data, and Methodology: Quantitative methods and questionnaires were used to collect sample data. Before distribution, the questionnaire underwent content validity and reliability testing through item-objective congruence and pilot tests. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were employed to analyze the data, validate the model's goodness of fit, and establish the causal relationship among variables for hypothesis testing. Results: The findings of this study demonstrate that system quality, confirmation, service quality and perceived usefulness are identified as the most significant factors influencing e-learning satisfaction and continuance intention among students. E-learning satisfaction was found to be the most influential predictor of continuance intention, both directly and indirectly. However, information service has no significant influence on students’ satisfaction. Conclusions: Based on these findings, it is recommended that developers of cloud-based e-learning systems in higher education institutions prioritize the enhancement of quality factors to ensure students perceive the system as useful. This, in turn, will further enhance perceived usefulness and continuance intention towards using cloud-based e-learning systems.